Study of Economic Burden and Health Care Resource Utilization by Chronic Obstructive Pulmonary Disease Patients in a Tertiary Care Hospital in Western India - Shah, Meenakshi; Godbole, Varsha; Patel, Tejas K; Patel, Tejas R (National Journal of Community Medicine, 2017)
Introduction: Chronic obstructive pulmonary disease (COPD) is a leading cause of death and disability worldwide and accounts for a huge financial burden on health care resources. This study was done over a one year period to determine the cost burden due to COPD, demographic profile and different treatment protocols. Methods: This cross sectional study included data from 200 patients diagnosed with COPD. This included the data for emergency visits, hospitalization, daily medications used and the costs incurred by the patients. In addition indirect cost burden for work days lost were also calculated. Results: The average OPD visits per patient per year were 11.32. Emergency room visits were required for almost 50% of the patients. Average admission rate was 1.45 per patient per year. The mean costs incurred per COPD patient per year was Rs. 5654.16 in government set up and Rs. 35,290.28 for private setup. Average loss of work days per patient was 16.45 days per year. Conclusions: COPD is a huge economic burden to the society. Major costs incurred are due to recurrent hospital admissions for exacerbations. Early diagnosis and proper treatment can significantly reduce the economic burden of the disease and help in efficient utilization of health care resources.